2020
DOI: 10.23919/jcc.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

NOMA-based UAV-aided networks for emergency communications

Abstract: High spectrum efficiency (SE) requirement and massive connections are the main challenges for the fifth generation (5G) and beyond 5G (B5G) wireless networks, especially for the case when Internet of Things (IoT) IoT devices are located in a disaster area. Non-orthogonal multiple access (NOMA)-based unmanned aerial vehicle (UAV)-aided network is emerging as a promising technique to overcome the above challenges. In this paper, an emergency communications framework of NOMAbased UAV-aided networks is established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Herein, the authors propose a novel power allocation strategy to maintain a balance between the system throughput and performance fairness. [27] proposes a framework for NOMA based UAV aided network to achieve high spectral efficiency and massive connections during emergency situation. The paper considers both single UAV and multi-UAV assisted networks and develops a joint trajectory and power optimization scheme to provide reliable services for both the cases.…”
Section: A Related Workmentioning
confidence: 99%
“…Herein, the authors propose a novel power allocation strategy to maintain a balance between the system throughput and performance fairness. [27] proposes a framework for NOMA based UAV aided network to achieve high spectral efficiency and massive connections during emergency situation. The paper considers both single UAV and multi-UAV assisted networks and develops a joint trajectory and power optimization scheme to provide reliable services for both the cases.…”
Section: A Related Workmentioning
confidence: 99%
“…Likewise, at very high v XZ and/or f c and/or τ , ρ XZ tends to 0, yielding severe channel time variations, in which the estimated CSI is completely uncorrelated with the actual one. Also, it worth mentioning that J 0 (x) in (6), with x = 2πv XZ fcτ c , is a decreasing function of v XZ and/or f c and/or τ over x ∈ [0, x 0 ] , with x 0 = 3.8317 being the function's minima that can be found numerically by retrieving the first zero of (J 0 (x)) .…”
Section: E Notationsmentioning
confidence: 99%
“…Nonetheless, despite the aforesaid features and applications, guaranteeing a fair functioning of such IoT networks is challenging in underserved areas (e.g., deserts, mountains), or in disaster zones non-covered by wireless cellular infrastructure [3], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Simulation results demonstrated that the combination of SWIPT and NOMA could further improve the EE of the communication network. Based on the prior works on NOMA-enabled wireless networks, the applications of UAVs within NOMA networks can further improve the system throughput since they can shorten the transmission distance and increase the channel gain [17]- [19]. In [17], the authors investigated the time sharing (TS) NOMA networks, and developed a resource allocation algorithm to maximize the EE of the UAV-TS-NOMA networks.…”
Section: Introductionmentioning
confidence: 99%
“…To guarantee the quality of service (QoS), the authors developed a data collection optimization algorithm using the generalized benders decomposition methods. The authors in [19] studied the UAV-assisted NOMA networks for emergency communications. Firstly, a deep-Q-learning-based scheme was proposed to maximize the sum rate of the UAV-enabled uplink NOMA networks.…”
Section: Introductionmentioning
confidence: 99%